2022
DOI: 10.1155/2022/4987912
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Potential of Neurokinin 1 Receptor in Breast Cancer and Its Relationship with Ki-67 Index

Abstract: Background. Neurokinin 1 receptor (NK1R) is a promising biomarker and therapeutic target in breast cancer. This study was aimed at investigating the expression level of NK1R in breast cancer tissues and its relationship with proliferation index as measured by Ki-67, clinicopathological characteristics of patients, and overall survival rate. Methods. Immunohistochemical expression of NK1R and Ki-67 was measured in 164 paraffin-embedded breast cancer tissues of four molecular subtypes (42 HER2-enriched, 40 lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A further analysis showed that peak time was more lowly expressed in high Ki-67 patients and more highly expressed in high ER and PR patients. As a high Ki-67 index is a risk factor for a poor prognosis in patients ( 21 ), while high ER and PR expression levels are protective factors for a poor prognosis ( 22 - 24 ), we indirectly illustrated that peak time is associated with patient prognosis.…”
Section: Discussionmentioning
confidence: 87%
“…A further analysis showed that peak time was more lowly expressed in high Ki-67 patients and more highly expressed in high ER and PR patients. As a high Ki-67 index is a risk factor for a poor prognosis in patients ( 21 ), while high ER and PR expression levels are protective factors for a poor prognosis ( 22 - 24 ), we indirectly illustrated that peak time is associated with patient prognosis.…”
Section: Discussionmentioning
confidence: 87%
“…Tumor size and lymph-node metastasis relate to the number of fibers containing SP [96][97][98]. In breast cancer, the overexpression of SP is associated with a negative prognostic value, the expression of NK-1R with a high Ki-67 index (the nuclear Ki-67 protein is related to proliferative mechanisms), and higher tumor grade [99,100]. The data suggest that NK-1R and SP may serve as predictive cancer factors.…”
Section: The Substance P/neurokinin-1 Receptor System As a Cancer Pre...mentioning
confidence: 91%
“…Indeed, several studies have demonstrated that neuropeptide receptors are expressed on tumor cells, and their binding to neuropeptide ligands regulates various processes, including proliferation, survival, adhesion, and migration. This is particularly noteworthy, which have been shown to be involved in the progression of various cancer types, as shown in gastric, breast, and oral cancers, namely, through binding of SP to NK-1R expressed by tumor cells (213,221,(229)(230)(231)(232)(233)(234)(235)(236)(237)(238)(239)(240)(241)(242). Thus, sensory innervation could affect tumor growth not only by acting on tumor cells but also on tumor vascularization.…”
Section: Influence Of Sensory Neurons On Cancer Growthmentioning
confidence: 99%